The role of macrophage colony-stimulating factor (M-CSF) in prognosis, diagnosis and in the treatment of epithelial ovarian cancer - Szczylik, Cezary; Wcisło, Gabriel; Bodnar, Lubomir; Miedzińska-Maciejewska, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2003)
Ovarian cancer is the leading cause of death in women from gynecological malignancies. This comes from the advanced stage disease at the diagnosis that, in turn, is the result of scanty significant symptoms. The lack of prognostic factors to detect an early stage of the disease is a causative event that ovarian cancer has enough time to spread out. Therefore, most ovarian cancer patients appear at advanced stages. Hence there is a great need to find out novel parameters which could be used as prognostic factors. One of the parameters is macrophage-colony stimulating factor (M-CSF or CSF-1, first discovered colony stimulating factor). The aim of the overview is to show the structure, mechanisms of activity and brief biology of M-CSF (macrophage-colony stimulating factor) especially in the case of ovarian cancer. Prognostic and predictive factors appear to be of clinical interest to determine the accurate history of a particular case of ovarian cancer. Furthermore, the scope of the overview is to appraise the role of M-CSF and its receptor measurements as a prognostic or predictive factor. M-CSF levels were assayed either in serum or ascites in primary ovarian cancer and metastases located in ovaries as well. We decided to hint at the potential role of M-CSF as the adjunctive therapy after chemo regimen complications, for instance febrile neutropenia. The potential role of M-CSF as the diagnostic marker and therapeutic drug is warranted but further studies are necessary to improve its clinical interest.